Reported care quality in federal Ryan White HIV/AIDS Program supported networks of HIV/AIDS care. - Hirschhorn, Lisa R; Landers, Stewart; McInnes, D Keith; Malitz, Faye; Ding, Lin; Joyce, Rebecca; Cleary, Paul D (AIDS care, 2009)
Since 1991, the US Government has funded medical and support services for people living with HIV and AIDS (PLWHA) through the Ryan White HIV/AIDS Program. The Ryan White Program supports networks of care which include medical care providers and support services for PLWHA in 51 Eligible Metropolitan Areas (EMAs). In the 2000 reauthorization of the Ryan White Program, quality management programs were required for all sites receiving funding. To facilitate quality management and improvement activities in EMAs, we developed a set of surveys to measure characteristics of care networks and the quality, accessibility, and coordination of services from the perspective of case management and medical providers, administrators and consumers. The surveys measured quality management and support activities of the entire network, as well as reported quality of services at individual care sites. They were administered in 42 EMAs from a total of 43 who had not participated in earlier pilot testing and were located in the continental US. The care networks were rated highly on access, quality, and coordination between case management and primary care providers. However, there were frequently differences in ratings of quality and barriers by type of respondent (consumer representatives, Grantees, and providers). There were also substantial variations across EMAs in network characteristics, perceived effectiveness, performance measurement, and quality improvement activities. The results indicate that the Ryan White Program has been successful in some areas of developing networks of care, but additional support is needed to strengthen the comprehensiveness and coordination of care. Additional work also is needed to better define and measure the essential characteristics of coordinated and integrated networks of care and assess whether those characteristics are related to access and quality of care and services.
Keywords: Adult; Analysis of Variance; Delivery of Health Care; Female; HIV Infections; Humans; Information Services; Interprofessional Relations; Male; Middle Aged; Patient Satisfaction; Professional-Patient Relations; Quality of Health Care; United States; Urban Health